Passive acoustic monitoring data recorded by recorder SV1059 at mooring AWI232-12 in the Weddell Sea, Southern Ocean, in 2015 - Thomisch, Karolin; Spiesecke, Stefanie; Lefering, Katharina; Mattmüller, Ramona; Van Opzeeland, Ilse; Zwicker, Sarah; Boebel, Olaf (PANGAEA, 2024)
Passive acoustic monitoring (PAM) data were collected by recorder SV1059 of type Sono.Vault (manufactured by develogic GmbH, Hamburg, Germany) at 68.9815° S, 0.0833° W, mooring AWI232-12, in the Weddell Sea, Atlantic sector of the Southern Ocean. During a deployment period from December 2014 to December 2016, passive acoustic data were collected from January 2015 to August 2015 (recording period) by SV1059 as part of the Hybrid Antarctic Float Observing System (HAFOS) in the Weddell Sea. The recorder was moored at 999 m depth and scheduled to record continuously at a sample rate of 6,857 Hz. Further details about the data acquisition and processing of this data set can be found in the accompanying metadata file (see Additional metadata) as well as the data processing report (see Data Processing Report). Passive acoustic data archived here represent data processing Level 2+ (see Data Processing Report), deviating from Standard Operation Procedure (SOP) Glossary (Thomisch et al. 2023a). Further information on data processing with regard to data preparation and standardization can be found in the associated SOP Part 1: Data preparation and standardization (Thomisch et al. 2023b).